Model Penyelesaian Sengketa Pada Masyarakat Desa Pulau Sewangi Yang Berbasis Lahan Basah - Erliyani, Rahmida; Syahrida, Syahrida; Rahmawati, Diana; Sihite, Dermawati (Magister Kenotariatan, Universitas Jambi, 2025)
Law Number 3 of 2024, as an amendment to Law Number 6 of 2014, affirms the authority of village heads in resolving community disputes. This study examines the dispute resolution model in the Pulau Sewangi Village community, Barito Kuala Regency, South Kalimantan, which has a wetland-based cultural characteristic with communal life along the Barito River. The study used an empirical legal method with a socio-legal approach through interviews and field observations. The results show that the presence of the village head plays a central role in maintaining social harmony through non-litigation dispute resolution, which is more dominant than litigation. The settlement model implemented prioritizes deliberation based on local wisdom, which is directed at forms of mediation and conciliation. However, for certain cases that meet criminal elements, the village head coordinates with law enforcement officials towards the litigation process. Thus, the dispute resolution model in Pulau Sewangi Village reflects the synergy between formal legal approaches and local wisdom, which is relevant to the development of village governance based on wetland community culture.